The first evidence of subgroup IB isolates of Cucumber mosaic virus in Ukraine - Shevchenko, T.P.; Tymchyshyn, O.V.; AlDalain, E.; Bysov, A.S.; Budzanivska, I.G.; Shevchenko, O.V.; Polishchuk, V.P. (2015)
Aim. In current work, we proceeded with the strain attribution of Ukrainian isolates CMV based on the phylogenetic analysis of the partial sequences of the coat protein gene. Methods. ELISA, RT-PCR, DNA sequencing and phylogenetic analysis. Results. Cucumber mosaic virus (CMV) is widespread among the variety of crops from the Cucurbitaceae and Solanaceae families in Ukraine. The symptomatic samples from different regions of Ukraine were collected and tested for the presence of CMV. The coat protein (CP) gene of two isolates was amplified and sequenced. The partial nucleotide sequences of CP gene were determined and compared to those of other CMV strains belonging to the IA, IB and II subgroups. Comparison of the nucleotide sequences of Ukrainian isolates showed their similar identity percentages and close relationships with the subgroup IB strains from other countries. The highest nucleotide homology was shared with the strains ABI (Korea) and SD (China). Conclusions. Based on the highest identities of the coat protein gene sequences and close phylogenetic relationships with the subgroup IB members of CMV, the Ukrainian isolates under study were identified as belonging to the subgroup IB. Our findings show for the first time an occurrence of the IB subgroup isolates of CMV in Ukraine. Мета. Встановлення штамової приналежності українських ізолятів вірусу огіркової мозаїки (ВОМ) на основі філогенетичного аналізу фрагмента послідовності гена капсидного білка. Методи. Імуноферментний аналіз (ІФА), полімеразна ланцюгова реакція зі зворотною транскрипцією (ЗТ-ПЛР), сиквенування ДНК та філогенетичний аналіз. Результати. ВОМ є широко розповсюдженим патогеном сільськогосподарських культур в Україні. Були відібрані й проаналізовані зразки рослин з вірусоподібними симптомами представників родин Cucurbitaceae і Solanaceae. Виходячи з результатів візуальної та серологічної діагностики, два зразки Lycopersicon esculentum і Cucurbita pepo з Полтавської області були обрані для подальших молекулярних досліджень. Були ампліфіковані й сиквеновані часткові послідовності гена капсидного білка. Отримані послідовності кДНК гена капсидного білка цих ізолятів порівняли з опублікованими в Генбанку послідовностями штамів ВОМ різних підгруп. Найбільша гомологія українських ізолятів продемонстрована зі штамами ВОМ підгрупи ІВ. Найбільш спорідненими до українських ізолятів виявилися штам АВІ з Кореї та штам SD з Китаю. Висновки. Спираючись на результати філогенетичного аналізу, можна стверджувати, що детектовані українські ізоляти вірусу огіркової мозаїки належать до групи ІВ. Наші результати є першим повідомленням про наявність ізолятів ВОМ підгрупи ІВ на території України. Цель. Установить штаммовую принадлежности украинских изолятов вируса мозаики огурца (ВМО) на основании филогенетичного анализа частичной последовательности гена капсидного белка. Методы. Иммуноферментный анализ (ИФА), полимеразная цепная реакция с обратной транскрипцией (ОТ-ПЦР), секвенирование ДНК и филогенетический анализ. Результаты. ВМО широко распространён в Украине среди сельскохозяйственных культур. Были отобраны и проанализированы образцы растений с вирусоподобными симптомами семейств Cucurbitaceae и Solanaceae. На основе визуальной и серологической диагностики два образца Lycopersicon esculentum и Cucurbita pepo из Полтавской области были избраны для дальнейших молекулярных исследований. Были амплифицированы и секвенированы частичные последовательности гена капсидного белка. Проведено сравнение полученных последовательностей кДНК гена капсидного белка этих изолятов с опубликованными в Генбанке последовательностями штаммов ВМО различных подгрупп. Наибольшая гомология украинских изолятов продемонстрирована с представителями подгруппы ІВ. Наиболее родственными к украинским изолятам показаны штаммы АВІ (Корея) и SD (Китай). Выводы. Исходя из результатов филогенетического анализа, украинские изоляты ВОМ принадлежат к подгруппе ІВ. Результаты этой работы являются первым свидетельством присутствия изолятов подгруппы ІВ ВМО на территории Украины.